Kidnapped and Made Brides: Advancing Quantum Reparation for Sexual and Gender-based Victims in Conflict Zones - Adeniyi, Olayinka Oluwakemi (European Scientific Journal, ESJ, 2021)
Conflict is the friction resulting from incompatibilities among people. Conflict has become a common experience in many African countries today which has led to bloodshed, death, starvation, famine, and ravaged communities. In this scenario, women and children have always been the worst hit. The girl child, particularly, and women are sexually abused, raped, kidnapped, and sometimes converted to sex slaves or forced into marriages. Since 2009, Boko Haram, a group of notorious terrorists, has been operating in the Northern part of Nigeria. One major feature of the signage of the group is the abduction of girls and women whom they forced into sexual slavery and marriage. In the years following the onslaughts, many of these girls were returned based on negotiations with the Federal Government of Nigeria. Some of the girls were returned defiled, some with children, and some with pregnancies as evidences of their sex slavery experience in the hands of the insurgents and abductors. While the Boko Haram troop’s attack is still an ongoing experience in Nigeria, little or nothing, however, is relayed about the issue of reparation for the girls and women returnees. Access to justice is one major factor that has not been provided for the victims. Using a desktop research, existing literature is reviewed in an analytical and comparative methodology, as available legal provisions are examined. It is suggested to the Nigerian government to involve the victims in the discourse of reparation and ensure their access to justice. This will ensure that quantum reparation is provided. The paper will be of immense importance to the Nigerian government, policymakers, civil organizations, human rights practitioners, the victims, as well as the citizenry. It will contribute in the way of education and policy making to the mentioned people.